2020
DOI: 10.28945/4475
|View full text |Cite
|
Sign up to set email alerts
|

The Validation of Using Assessment Tools and a Theory to Mentor Doctoral Students with Integrity and Trustworthiness

Abstract: Aim/Purpose: The primary aim of this study was to reveal the assessment tools and a theory preferred to mentor doctoral students with integrity and trustworthiness. The connection between mentors’ feelings of trustworthiness and protégé success were explored. Background: This study examines the concept presented in 1983, 1985, and 1996 by Kram of mentor relations (MR) theory, which illustrates that graduation rates can improve with effective mentoring. In the United States, doctoral programs have low graduati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 46 publications
1
14
1
1
Order By: Relevance
“…Empirical data have shown that protégés were more open to learning from trustworthy mentors (Fleig-Palmer & Schoorman, 2011). For example, according to mentors, doctoral protégés are more likely to graduate and are more likely to achieve at a high level when a trustworthy mentor is present (Roberts, 2020). The current study adds to this work by revisiting the relationship between mentors' trustworthiness and protégé success when these variables are measured from the point of view of the protégé.…”
Section: Mentors' Integrity and Trustworthiness -Mit Sub-theorymentioning
confidence: 83%
See 3 more Smart Citations
“…Empirical data have shown that protégés were more open to learning from trustworthy mentors (Fleig-Palmer & Schoorman, 2011). For example, according to mentors, doctoral protégés are more likely to graduate and are more likely to achieve at a high level when a trustworthy mentor is present (Roberts, 2020). The current study adds to this work by revisiting the relationship between mentors' trustworthiness and protégé success when these variables are measured from the point of view of the protégé.…”
Section: Mentors' Integrity and Trustworthiness -Mit Sub-theorymentioning
confidence: 83%
“…Thus, the researcher adapted Tschannen-Moran's instrument to assess trustworthiness in the context of doctoral student mentoring. In a prior study, the researcher presented a new instrument designed to measure doctoral mentors' perceptions of their own trustworthiness (Roberts, 2020). In the current study, the researcher will present a parallel new instrument designed to measure mentors' trustworthiness from the point of view of the protégé.…”
Section: Mentors' Integrity and Trustworthiness -Mit Sub-theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The editors of all chemical journals are also involved in judging the quality of submitted papers. The subject has caught the attention of many scientists expressing their views in essays, and only a few are cited here [2–8] . As pointed out by a reviewer of this essay, a crucial aspect in judging the quality of scientific output is often forgotten, namely the explosion of the number of scientists in the world during the last 100 years and before, as first put forth by Derek J. de Solla Price in 1963 [9] and restated in 1986 [10] .…”
Section: Introductory Remarksmentioning
confidence: 99%